In situ stress conditions at IODP Site C0002 reflecting the tectonic evolution of the sedimentary system near the seaward edge of the Kumano basin, offshore from SW Japan. Issue 5 (15th May 2017) - Song, Insun; Chang, Chandong
Abstract: This paper presents a complete set of in situ stress calculations for depths of 200–1400 meters below seafloor at Integrated Ocean Drilling Program (IODP) Site C0002, near the seaward margin of the Kumano fore‐arc basin, offshore from southwest Japan. The vertical stress component was obtained by integrating bulk density calculations from moisture and density logging data, and the two horizontal components were stochastically optimized by minimizing misfits between a probabilistic model and measured breakout widths for every 30 m vertical segment of the wellbore. Our stochastic optimization process reveals that the in situ stress regime is decoupled across an unconformity between an accretionary complex and the overlying Kumano fore‐arc basin. The stress condition above the unconformity is close to the critical condition for normal faulting, while below the unconformity the geologic system is stable in a normal to strike‐slip fault stress regime. The critical state of stress demonstrates that the tectonic evolution of the sedimentary system has been achieved mainly by the regionally continuous action of a major out‐of‐sequence thrust fault during sedimentation in the fore‐arc basin. The stable stress condition in the accretionary prism is interpreted to have resulted from mechanical decoupling by the accommodation of large displacement along the megasplay fault. Key Points: A full set of in situ stress magnitudes was determined for IODP Hole C0002A by a stochastic process In situ horizontal stresses are decoupled across the unconformity between the Kumano fore‐arc basin and underlying accretionary prism The state of in situ stresses in the Kumano basin reflects tectonic interactions between the sedimentary system and a megasplay fault